A rancher of her own - Daille, Barbara White; Thacker, Cathy Gillen (Sydney, NSW : Harlequin Mills & Boon, 2016)
A rancher of her own: Ranch manager Pete Brannigan has no interest in playing tour guide to a city slicker Jane Garland but it is his chance to get everything her grandfather has given the single dad. Though Pete's drawn to Jane, he won't hurt his young children by falling for another woman who puts her career before family. Jane's seen the world through her camera and used it to shield her emotions. With Pete, she can finally let her guard down. If only he could do the same. Despite their powerful bond, Pete still can't trust Jane with his kids or his heart. But if he keeps pushing her away, he may ruin any chance their relationship has to develop.
The Texas wildcatter's baby: Ginger Rollins can't believe she gave in to temptation - again! It's time for her and Rand McCabe to face the consequences. Never mind that the geological engineer and sexy environmental cowboy are complete opposites. Now that she's pregnant, they have one option. Rand isn't used to being proposed to by a woman - especially Ginger - but he's all for getting married. But the independent wildcatter sees their union as just a deal. Doesn't she know they share more than chemistry? Rand vows to love and honour Ginger forever and it's a promise he intends to keep.
A rancher of her own / Barbara White Daille ©2015 -- The Texas wildcatter's baby / Cathy Gillen Thacker ©2014.
"2 great reads" --Cover.
Keywords: Romance fiction; Man-woman relationships -- Fiction; Pregnant women -- Fiction; Marriage -- Fiction; Ranchers -- Fiction; Single fathers -- Fiction; Women photographers -- Fiction